Strategi dan Nilai-Nilai Ekonomi Islam dalam Promosi Foodies di Kota Palangka Raya - Kurniawan, Rahmad; Ihsan, Moh; Fitri, Fitri (Journal of Industrial and Syariah Economics, 2024)
The digital era has transformed many aspects, including the shift in promotional methods from print media to digital platforms. One of the social media platforms that has been widely utilized is Instagram. Over time, Instagram has also become a venue for promotion. Various types of businesses are promoted through Instagram, one of which is the promotion via foodies accounts that have attracted the interest of various culinary entrepreneurs. This research aims to understand the promotional strategies of foodies in Palangka Raya from the perspective of Islamic economics. This study is a field research employing a descriptive qualitative approach. The subjects of this research are the owners of foodies accounts @kulinerpalangka, @abang.lapar, and @ngunyah.pky in Palangka Raya, as well as three informants who use foodies services. The research results indicate that social media marketing activities for foodies maximize the 4 Cs in using social media for promotion, namely context, communication, collaboration, and connection. The Islamic economic perspective on foodies' activities emphasizes cooperation between business actors and foodies. Users of food services must meet the halal review criteria. The verse discussing the halal nature of a product is QS Al-Baqarah verse 29. Additionally, the concept of foodies includes an element of excessive eating, which contradicts Islamic teachings as stated in QS Al-A'raf verse 31